Structural Analysis Of Thermoformed Electroluminescent Printed Lighting - Chiang, Han Xi (Universiti Sains Malaysia, 2019)
Printed electronic is an emerging technology which the electronic devices are printed on various type of substrates. The flexibility of the printed electronics have enabled the shaping of these flexible electronic if they are printed on flexible substrate. Thermoforming process has been introduced into the shaping of printed electroluminescent(EL) on the plastic substrate. The main objective of this project is to study the effect of thermoforming on the EL printed thermoplastic by utilising ANSYS Polyflow simulation and Scanning Electron Microscope(SEM). Simulation of the thermoforming process was done on a polyethylene terephthalate(PET) sheet to obtain the thickness distribution on the simulated PET sheet. At the same time, the thermoformed product was experimented using SEM to obtain the thickness distribution of thermoformed product. The result from both approach showed that there were different deviations in thickness at the different area of the thermoformed product. However, the difference was acceptable due to the complex and curvature design of the mold. Energy dispersive X-ray was done to determine the composition of element in the thermoformed product. The results showed that the distribution of EL materials were uneven after thermoforming process but the layers could still be detected by analysing the composition of element in the layers. In conclusion, thermoforming process is a suitable process for the shaping of printed electronics on the thermoplastic substrate.